Psychological needs assessment of primary school going students of Dhaka (Dhaka University Journal of Biological Sciences, 2021)
The present study was conducted with the following objectives: (a) assessing the mental health and psychological understanding among the primary school going students through the respective stakeholder's views, (b) investigating the psychological needs of primary school going students, (c) identifying the gaps between provided psychological services and required demands among students and (d) collecting relevant and consistent data and information to plan future interventions and produce hypothesis for further study. Since it was a qualitative study, 16 focus group discussions (FGDs), 39 interviews, and several observations in four schools were made with 123 purposive samples (73 primary school going students, 21 parents, and 29 mental health workers and other staff). For the assessment, two self-made guidelines for different stakeholders and thematic analysis for data analysis were used in this present study. The results showed that most of the primary school going especially the govt. and madrasah going students are not aware of their mental health while bearing a lot of symptoms of behavioral, emotional, and psychological issues, but students from private English medium schools possess sound knowledge about it. The results also indicated that there is a huge gap between psychological burdens and provided services. The absence of culturally validated assessment tools and intervention techniques, collaboration among different professionals, and lack of subject experts and funds were also evident. Thus, to have healthy and welladjusted future generations, measures should be taken immediately.Dhaka Univ. J. Biol. Sci. 30(2): 243-259, 2021 (July)